2020
DOI: 10.1001/jamanetworkopen.2020.4514
|View full text |Cite
|
Sign up to set email alerts
|

Indication-Specific Opioid Prescribing for US Patients With Medicaid or Private Insurance, 2017

Abstract: IMPORTANCE Although opioids can be effective medications in certain situations, they are associated with harms, including opioid use disorder and overdose. Studies have revealed unexplained prescribing variation and prescribing mismatched with patient-reported pain for many indications. OBJECTIVE To summarize opioid prescribing frequency, dosages, and durations, stratified across numerous painful medical indications. DESIGN, SETTING, AND PARTICIPANTS Retrospective cross-sectional analysis of 2017 US administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…The literature has raised three issues with existing guidelines for opioid prescription, particularly the CDC guidelines [ 11 ]: Providers do not have a clear idea about how to easily implement these guidelines in their practices or there exist uncertainties surrounding the impact of the recommendations on patient pain levels, particularly in the presence of comorbidities [ 27 ]. Across different specialties/medical conditions, (i) there is no consensus among providers in selecting optimal treatments, and (ii) there are various perspectives on how opioids are deemed appropriate, resulting in many of the providers not aligning with the guidelines and/or significant variations among them in opioid prescription [ 28 , 29 , 30 ]. On a similar note, emergency departments (EDs) are shown to be more aligned with the CDC guidelines than non-EDs [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has raised three issues with existing guidelines for opioid prescription, particularly the CDC guidelines [ 11 ]: Providers do not have a clear idea about how to easily implement these guidelines in their practices or there exist uncertainties surrounding the impact of the recommendations on patient pain levels, particularly in the presence of comorbidities [ 27 ]. Across different specialties/medical conditions, (i) there is no consensus among providers in selecting optimal treatments, and (ii) there are various perspectives on how opioids are deemed appropriate, resulting in many of the providers not aligning with the guidelines and/or significant variations among them in opioid prescription [ 28 , 29 , 30 ]. On a similar note, emergency departments (EDs) are shown to be more aligned with the CDC guidelines than non-EDs [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Across different specialties/medical conditions, (i) there is no consensus among providers in selecting optimal treatments, and (ii) there are various perspectives on how opioids are deemed appropriate, resulting in many of the providers not aligning with the guidelines and/or significant variations among them in opioid prescription [ 28 , 29 , 30 ]. On a similar note, emergency departments (EDs) are shown to be more aligned with the CDC guidelines than non-EDs [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is a paucity of studies on stand-alone morphine use in pain management of chronic disorders other than SCD during hospitalization. Studies conducted regarding opioid use in pain treatment have revealed various results concerning measurement and reporting of opioid use in hospitalized patients including delays and barriers in the administration of these analgesics [ 38 ]. In this review, morphine use among SCD patients hospitalized in VOC varied based on the measurement used by researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The distinctive challenges in managing the complications of VOC resulted in CDC recommendations to refer to SCD specific guidelines for pain management. However, misapplication of CDC guidelines was observed, resulting in the CDC’s emphasis of treating the pain of SCD beyond the scope of their recommendations [ 38 ]. Considering the CDC’s recommended guidelines, SCD specific guidelines [ 38 ] and the dosages reported by researchers in studies that are included in this review, there appears to remain a gap in practice regarding what is recommended and ultimately prescribed dosing in adults hospitalized in VOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation